2016
DOI: 10.5213/inj.1632558.279
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Nocturia and Nocturnal Polyuria: Can New Cutoff Values Be Suggested According to Age and Sex?

Abstract: PurposeThe aims of this study were to assess the prevalence of nocturia and nocturnal polyuria (NP) and to define new cutoff values according to age and sex for both conditions.MethodsData from a population-based prevalence survey conducted among a random sample of 2,128 adults were analyzed in this study. Participants were requested to fill out a questionnaire including the International Continence Society (ICS) definitions of lower urinary tract symptoms and the International Consultation on Incontinence Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Liew and colleagues reported that the prevalence of nocturia among Singaporean adults was 55% [13]. Meanwhile, the reported prevalence were 46% in the Dutch population [14], 31% in the US population [5] and 28.4% in the Turkish population [15]. In the present study, there was a signi cant higher prevalence among women.…”
Section: Discussionsupporting
confidence: 46%
“…Liew and colleagues reported that the prevalence of nocturia among Singaporean adults was 55% [13]. Meanwhile, the reported prevalence were 46% in the Dutch population [14], 31% in the US population [5] and 28.4% in the Turkish population [15]. In the present study, there was a signi cant higher prevalence among women.…”
Section: Discussionsupporting
confidence: 46%
“…In fact, nocturia has not been defined at all in many studies. The new definition reflects the fact that nocturia is first a symptom, which may or may not be a complaint (ie, of an abnormality), with mixed and multiple etiologies and a prevalence in the general population which is well described for men and women of different ages worldwide …”
Section: Nocturnal Symptomsmentioning
confidence: 99%
“…The new definition reflects the fact that nocturia is first a symptom, which may or may not be a complaint (ie, of an abnormality), with mixed and multiple etiologies and a prevalence in the general population which is well described for men and women of different ages worldwide. 2,15,16 Night-time frequency can sometimes be confused with nocturia. However night-time frequency includes voids when an individual goes to bed, with the intention of sleeping, but cannot sleep and needs to void at least once before falling asleep (2002 nocturia document).…”
Section: -H Polyuria (Not Changed)mentioning
confidence: 99%
“…Age distribution, the definition of NP, and comorbidities (e.g. hypertension, congestive heart failure, and excessive evening fluid intake) have the potential to affect the prevalence rate of NP . A high proportion of patients aged ≥70 (40%) in the present study may explain the higher prevalence of NP.…”
Section: Discussionmentioning
confidence: 75%